Unlocking potential: the role of the electron transport chain in immunometabolism - O'Neill, Luke (My University, 2024)
The electron transport chain (ETC) couples electron transfer with proton pumping to generate ATP and it also regulates particular innate and adaptive immune cell function. While NLRP3 inflammasome activation was initially linked to reactive oxygen species (ROS) produced from Complexes I and III, recent research suggests that an intact ETC fueling ATP is needed. Complex II may be responsible for Th1 cell proliferation and in some cases, effector cytokine production. Complex III is required for regulatory T (Treg) cell function, while oxidative phosphorylation (OXPHOS) and Complexes I, IV, and V sustain proliferation and antibody production in B lymphocytes, with OXPHOS also being required for B regulatory (Breg) cell function. Despite challenges, the ETC shows therapeutic targeting potential for immune-related diseases and in immuno-oncology.
PUBLISHED
Keywords: NLRP3 inflammasome activation; OXPHOS; electron transport chain (ETC); respiratory complexes; reactive oxygen species; mitochondria; adaptive immunity; immunometabolism; innate immunity